2012
DOI: 10.1158/0008-5472.can-11-2393
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Promote Liver Metastasis via Mac-1–Mediated Interactions with Circulating Tumor Cells

Abstract: Although circulating neutrophils are associated with distant metastasis and poor outcome in a number of epithelial malignancies, it remains unclear whether neutrophils play an active causal role in the metastatic cascade. Using in vivo models of metastasis, we found that neutrophils promote cancer cell adhesion within liver sinusoids and, thereby, influence metastasis. Neutrophil depletion before cancer cell inoculation resulted in a decreased number of gross metastases in an intrasplenic model of liver metast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
299
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(321 citation statements)
references
References 43 publications
5
299
2
2
Order By: Relevance
“…This effect was reversed when inflamed neutrophils were co-inoculated with tumor cells [307]. H-59 cells showed reduced adhesion to liver sinusoids of CD11b deficient mice [307]. In contrast, our own work, using mouse models of breast cancer, shows that neutrophils are stimulated by tumor-secreted factors and acquire an anti-tumor phenotype [32].…”
Section: Neutrophils In Pre-metastatic Organs -The "Seed and Soil" Hymentioning
confidence: 70%
See 2 more Smart Citations
“…This effect was reversed when inflamed neutrophils were co-inoculated with tumor cells [307]. H-59 cells showed reduced adhesion to liver sinusoids of CD11b deficient mice [307]. In contrast, our own work, using mouse models of breast cancer, shows that neutrophils are stimulated by tumor-secreted factors and acquire an anti-tumor phenotype [32].…”
Section: Neutrophils In Pre-metastatic Organs -The "Seed and Soil" Hymentioning
confidence: 70%
“…Neutrophil depletion prior to cancer cell inoculation reduced the number of liver metastases [307]. This effect was reversed when inflamed neutrophils were co-inoculated with tumor cells [307]. H-59 cells showed reduced adhesion to liver sinusoids of CD11b deficient mice [307].…”
Section: Neutrophils In Pre-metastatic Organs -The "Seed and Soil" Hymentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced retention of human melanoma cells in lungs can be seen as early as 24 hours after co-injection with neutrophils into nude mice 143 . In experimental lung or liver metastasis models where cancer cell lines are injected into the circulation or spleen, respectively, systemic depletion of neutrophils (via anti-Gr1 antibodies) reduces the formation of metastases 144,145 . Intravital imaging has shown that cancer cells colocalize with endothelial cell-associated neutrophils in a CD11b-dependent manner 144 , suggesting that neutrophils guide cancer cells into tissues and/or retain them there rather than supporting the outgrowth of secondary tumors.…”
Section: The Pro-metastatic Role Of Neutrophilsmentioning
confidence: 99%
“…In experimental lung or liver metastasis models where cancer cell lines are injected into the circulation or spleen, respectively, systemic depletion of neutrophils (via anti-Gr1 antibodies) reduces the formation of metastases 144,145 . Intravital imaging has shown that cancer cells colocalize with endothelial cell-associated neutrophils in a CD11b-dependent manner 144 , suggesting that neutrophils guide cancer cells into tissues and/or retain them there rather than supporting the outgrowth of secondary tumors. Neutrophils use neutrophil extracellular traps (NETs) for this purpose to sequester circulating cancer cells in a mesh of nucleic acids, antimicrobial factors and enzymes, and to promote adhesion at distant organ sites 146 .…”
Section: The Pro-metastatic Role Of Neutrophilsmentioning
confidence: 99%